Reduced sickness absence in regular commuter cyclists can save employers 27 million euros. - (:unkn) unknown (My University, 2009)
Employees who cycle regularly to work are less frequently ill, with on average more than one day per year less absenteeism than colleagues who do not cycle to work. If employers in the Netherlands were to encourage employees to cycle to work more, annual savings could reach 27 million euros. These results of the TNO study were presented on 26 January this year by the Dutch Secretary of State for the Ministry of Transport, Public Works and Water Management, Tineke Huizinga, during the FietsVak 2009 event in the Dutch town of Rosmalen.
Keywords: Individualverkehr; Fahrradverkehr; Untersuchung; Berufsverkehr; Gesundheitsförderung; Radfahren